The structure and activities of the Big Circle Boys in Canada - Chung, A (2016)
Scholars have long made two claims: ethnic-Chinese criminal entrepreneurs have replaced traditional organised crime in transnational criminal markets including in high-level drug trafficking; there is no discernible structure or commonality (other than the desire for profit) among these informally organised criminals. This study assesses the validity of these assertions by investigating the Big Circle Boys (BCB) in Canada, drawing on qualitative data gathered from the field and from official documents. The BCB is found to be a decentralised network of career criminals comprised of illegal immigrants from Guangzhou, China. Their numbers have been steadily declining since the late 1990s. Among other activities, the BCB are found to be mainly involved in the drug markets, where they have competitively dominated the heroin trade during the 1990s. They do not fit the models of organised criminal group or mafia, but are classified to be a communal business based on Natarajan and Belanger's (1998) typology; this is attributed to their highly connected and collaborative core network comprised of BCB individuals and BCB cell leaders. Other overlapping typological categories found in their cellular network include those of freelance criminal, family business, and corporation. The BCB's violent reputation is not found to be superficial due to documented violent conducts, despite the false perpetuation of this image at times by non-BCB criminals. Internally, the BCB are capable of managing relations and resolving disputes without resorting to violence. The sources of their trust are derived from a combination of achieved and preordained ties, both of which have strong (sub)cultural underpinnings in the Chinese notion of guanxi and the Western concept of social capital. A third BCB generation is not likely to emerge primarily due to the lack of historical and sociocultural conditions which gave rise to the two earlier generations as explained by various classic criminological theories.